Advanced Air and Missile Defense under Spatial Grasp Technology - Sapaty, P.S. (Математичні машини і системи, 2017)
A novel control ideology and technology for solving tasks in large distributed networked systems will be briefed. Based on active scenarios self-navigating and self-matching distributed spaces in a highly organized super-virus mode, it can effectively establish global control over large systems of any natures. The technology can use numerous scattered and dissimilar facilities in an integral and holistic way, allow-ing them to work together in goal-driven supercomputer mode. The approach can be useful for advanced air and missile defense in a variety of ways, some of which described and explained in this paper. The re-lated material has been accepted for presentation at The 12th 3AF Integrated Air and Missile Defence in-ternational conference, June 27–29, Stockholm, Sweden, http://3af-integratedairmissiledefence.com.